Comparative analysis of chloroplast genomes on Meliaceae species: insights into the evolution and species identification - Nie, Zixuan; Ma, Jikai; Wang, Chengkun; Tang, Ming; Jia, Ting; Liao, Guoxiang; Zhang, Lu (Frontiers in Plant Science, 2025)
IntroductionMeliaceae, a significant group in Sapindales, possesses material and medicinal value due to its applications in timber and bioactive compounds. However, the high morphological diversity of the Meliaceae species and the lack of comparative studies of chloroplast (cp) genomes have led to great challenges in the classification and identification of Meliaceae species.MethodsIn this study, we sequenced the complete cp genomes of three Toona species (Toona fargesii, Toona ciliata, and Toona sinensis), and conducted comparative analyses of these cp genomes along with 29 previously published cp genomes of Meliaceae. Additionally, we performed the phylogenetic analyses and estimated the divergence times of Meliaceae.ResultsThe cp genomes of 32 Meliaceae species ranged from 158,558 bp to 160,978 bp in length. Specifically, the cp genomes of Toona varied from 159,242 bp to 159,617 bp in length. These cp genomes contained a total of 135 unique genes, comprising 90 protein-coding, 8 rRNA, and 37 tRNA genes. Divergence time estimation revealed that the Meliaceae family diverged into two subfamilies (Cedreloideae and Melioideae) approximately 72.92 Ma (95% HPD: 60.62-87.01 Ma) in the Late Cretaceous. The diversification of Cedreloideae (47.86 Ma, 95% HPD: 47.42-48.22 Ma) occurred later than that of Melioideae (66.60 Ma, 95% HPD: 55.41-79.73 Ma). Furthermore, comparative genomic analysis identified 52 to 116 simple sequence repeats (SSRs) and twelve highly variable regions (HVRs) found among the cp genomes of Meliaceae.DiscussionDivergence time estimation indicates that most Meliaceae species have a relatively recent origin, with rapid divergence occurring during the Late Oligocene or Early Miocene epochs. Comparative analysis of cp genomes revealed that Meliaceae exhibits relative conservation in terms of cp genome size, inverted-repeat (IR) boundary, genome structure, HVRs and codon patterns. Although differences exist between the Cedreloideae and Melioideae subfamilies, the overall similarity remains notably high. Furthermore, the ycf1, trnK-rps16, and ndhF-rpl32 regions exhibited the highest nucleotide polymorphism within Meliaceae, while the rpl22 gene displayed significant genetic diversity within both subfamilies. As candidate molecular markers, these regions may effectively distinguish among species. These findings not only provide insights into the evolution and species identification but also establish a scientific foundation for future systematics within Meliaceae.